Thirty-Five Years of Research on Climate Change, Sustainability, and Emergency Management: A Scientometric and Visualization Approach - Anbalagan, Muthuraj (Journal of Data Science, Informetrics, and Citation Studies)
This paper examines publications on Climate Change, Sustainability, and Emergency Management. The publication data were retrieved from the Web of Science Database as of December 31st, 2023. The study period spans from 1988 to 2023, covering 26 years of cited research publications. A total of 5,777 cited research publications were extracted and analysed across various categories. The bibliometrix package (R-4.3.1 for Windows) and the biblioshiny app were utilized for data analysis, while VOSviewer 1.6.19 was used for network analysis. The study aims to analyse the annual scientific production and impact, the top ten most productive authors, the top ten authors' research impacts, the top ten affiliations, the top ten most productive countries and their impact, the top ten countries by corresponding authors, the top ten journals and their impact, the top five journals' production over time, and the top ten highly cited research papers. It was found that 5,777 cited research publications were published from 2,301 sources. Notably, WANG Y has authored 59 research papers in the field of climate change, sustainability, and emergency management. Beijing Normal Univ has contributed 189 research publications. Furthermore, the United States of America has contributed 5,463 research articles and received the highest number of 42,004 total citations. The International Journal of Disaster Risk Reduction has published the highest number of articles (190) with an h-index of 29 and a g-index of 41, receiving 3,112 total citations since its inception in 2012.
Keywords: Citation Analysis; Climate Change; Emergency Management; Scientometrics; Sustainability; Web of Science Database.